Aromatherapy Cajuput Oil for Emesis Gravidarum - Eny Pemilu Kusparlina (Humanistic Network for Science and Technology (HNST), 2019)
Emesis Gravidarum can be very disturbing activity and impact on the maternal and fetal maternal obstacles. The incidence of emesis gravidarum in the world is 70-80% of the number of pregnant women, one non-pharmacological method that can reduce the intensity of nausea vomiting by cajuput oil. This research purposes to determine whether there is an influence of aromatherapy cajuput oil on emesis gravidarum in the first trimester pregnant women. This research used cross sectional approach. Population in this research is the first trimester pregnant woman which amounted to 17 pregnant women taken by using total sampling. The data were analyzed by univariate analysis with independent variable frequency distribution and dependent and bivariate analysis using Wilcoxon sign rank test. P-value value: 0.000 and alpha 0.005 Statistical test results show that cajuput oil has a significant effect on emesis gravidarum intensity. It can be concluded that there is an effect of Aromatherapy cajuput oil on emesisgravidarum in the first trimester pregnant woman, so it is expected that cajuput oil can be one of alternative non pharmacological method that can help to reduce the intensity of emesis gravidarum. Keywords: Pregnancy, Emesis gravidarum, Cajuput oil